2021
DOI: 10.1021/acs.jpca.1c03737
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect in the Reactions between Criegee Intermediates and 3-Aminopropanol

Abstract: Via intramolecular H atom transfer, 3-aminopropanol is more reactive toward Criegee intermediates, in comparison with amines or alcohols. Here we accessed the substituent effect of Criegee intermediates in their reactions with 3-aminopropanol. Through realtime monitoring the concentrations of two Criegee intermediates with their strong UV absorption at 340 nm, the experimental rate coefficients at 298 K (100−300 Torr) were determined to be (1.52 ± 0.08) × 10 −11 and (1.44 ± 0.22) × 10 −13 cm 3 s −1 for the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…This is different from the model used by Vereecken for CH 2 OO + HCl, where the (outer) barrier of the association was used as the bottleneck . In our recent study on the reaction between CIs and amino alcohol, we found that for syn -type CIs, the use of the inner barrier was valid to calculate the room temperature rate coefficient, while it failed for the anti -type CIs, such as CH 2 OO and anti -CH 3 CHOO . Considering these findings, we will use the inner barrier to calculate the rate coefficient for the present syn -CH 3 CHOO + HCl reaction.…”
Section: Computational Detailsmentioning
confidence: 80%
See 3 more Smart Citations
“…This is different from the model used by Vereecken for CH 2 OO + HCl, where the (outer) barrier of the association was used as the bottleneck . In our recent study on the reaction between CIs and amino alcohol, we found that for syn -type CIs, the use of the inner barrier was valid to calculate the room temperature rate coefficient, while it failed for the anti -type CIs, such as CH 2 OO and anti -CH 3 CHOO . Considering these findings, we will use the inner barrier to calculate the rate coefficient for the present syn -CH 3 CHOO + HCl reaction.…”
Section: Computational Detailsmentioning
confidence: 80%
“…In a recent study on the reaction of syn-type CIs with amino alcohol, we found that the explicitly correlated coupled cluster singles and doubles with perturbative triples, CCSD(T)-F12, with the F-12 optimized Dunning's correlation consistent triple valence basis set, 56 cc-pVTZ-F12 can give accurate energies. 57 Therefore, this method was also used to test the electronic energy corrections.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of CIs toward water, ,,,,,, alcohol, and similar molecules , shows very strong structure dependence with the reaction rate coefficients spanning a few orders of magnitude, depending on the structure and substituent groups of the CIs. However, the reactivity of CIs toward SO 2 and formic acid ,, molecules has a quite weak dependence on the CI structures.…”
Section: Introductionmentioning
confidence: 99%